Bibliometric analysis of immunogenic cell death in hepatocellular carcinoma - Jianming Sun; Chun Liu; Dongdong Liu; Xinlian Hu; Shirong Ren; Guoying Jiang; Daizhong Zhang; Shuai Hu; Xiaojing Yuan; Jun Tao (Discover Oncology)
Abstract Objectives This study aimed to delineate global research trends in immunogenic cell death (ICD) within hepatocellular carcinoma (HCC) by mapping collaborative networks, thematic shifts, and high-impact findings. Using VOSviewer network visualisation and R-bibliometrix quantitative metrics, we sought to show how scientific output has evolved and to pinpoint research gaps that may guide future investigations. Methods We retrieved 568 publications from the Web of Science Core Collection (2000–2024) using a tailored keyword strategy encompassing “Hepatocellular carcinoma” and “Immunogenic cell death.” Data were analyzed with VOSviewer and R-bibliometrix to visualize co-authorship patterns, keyword clusters, institutional collaborations, and citation metrics. Results Annual publication volumes rose markedly, peaking at 68 in 2023, and this quantitative surge parallels a qualitative shift toward clinically actionable research outputs. Over the entire period, the corpus accumulated 13 161 citations (mean 23.2 citations/article), indicating strong and growing academic influence. Keyword co-occurrence revealed three main clusters highlighting immunotherapeutic mechanisms, molecular pathways (e.g., HMGB1 and calreticulin), and epidemiological concerns. China and the United States led in overall output, with universities such as the University of California System, Harvard University, and Shanghai-based institutions forming robust collaborative networks. Highly cited articles, such as Zhong et al. (2016, Cell) on autophagy–inflammation crosstalk and Yu et al. (2020, ACS Nano) on mitophagy-augmented doxorubicin, underscored the role of autophagy, checkpoint inhibitors, and combination therapies in harnessing ICD to overcome HCC’s immunosuppressive microenvironment. These patterns indicate that the field is transitioning from descriptive bibliometrics to translational studies, signalling that forthcoming work will likely accelerate rational design of ICD-based clinical trials and inform funding priorities. Conclusion The findings confirm ICD as an emerging cornerstone of HCC research, with demonstrated capacity to reshape clinical-trial portfolios and refine biomarker-driven patient stratification, reflecting both deeper mechanistic insights and accelerating translational efforts. Ongoing challenges include refining biomarkers, integrating ICD inducers with immunotherapies, and accounting for HCC’s inherent complexities such as chronic liver disease and metabolic dysfunction. Future research directions focus on the use of nanotechnology for precise drug delivery, the integration of metabolomics and genomics data to enable personalised treatment, and the improvement of combination therapies combined with local interventions.